Research in the history of economic thought and methodology. Vol. 40, pt. A : including a symposium on David Gordon : American radical economist - Fiorito, Luca; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology ;, 2022)
Volume 40A of Research in the History of Economic Thought and Methodology features a symposium on the work of the radical economist David Gordon, edited by our own Luca Fiorito and featuring contributions from Nancy Breen, Richard McGahey, Robert Pollin, and Jim Stanford. The Volume also includes new general-research essays from Felix Schroeter, Ana Paula Londe Silva, and Seun Okunade.